Analysis of Student Learning Interest In Physics In Subject Force Material - Sofna, Ayu; Sakinah, Younanda; Misbah, Misbah; Pentang, Jupeth Toriano (International Journal of Education and Teaching Zone, 2023)
This study entitled "Analysis of Student Learning Interest in Physics in Force Material" aims to measure and determine the level of student interest in physics at SMA Negeri 11 Muaro Jambi. The method used by the researcher is a method in the form of a quantitative descriptive method with an instrument in the form of a student interest questionnaire. The population of this study were students in class X with a total of 32 students, students in class XI with a total of 33 students, and students in class XII with a total of 23 students. The sample technique used in this study is the total sampling technique. Researchers used a total sampling technique because the total population did not reach 100 students, so researchers used all students of class X, XII, and XII IPA 1, totaling 88 students as samples in this study. After the questionnaire was given to students and then calculated using Microsoft Excel, the results were obtained, then they were made into 4 categories with the final results in percent form and a bar chart was made. Based on the results that have been calculated, it is obtained that the level of student interest in physics class X IPA is in the good category which can be seen from Table 1 that as many as 46,8% of students have a high interest in physics subjects. Furthermore, students' interest in learning physics in class XI and XII IPA is in the low category which can be seen from Table 2 and Table 3 that 48,4% and 47,8% of students have a low interest in physics. In addition, students also do not understand the concept of force, classification of force and examples of force.